Determinants of Undergraduate Students’ Continuance Intention to Use E-learning of at a Public University in Chengdu, China - Wang, Yanjing (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This study aims to examine the students’ continuance intention of using e-learning platforms in a public university in Chengdu, China. Based on the Technology Acceptance Model (TAM), Information System Success Model (ISSM), and Expectation-confirmation Model (ECM), this study comprises seven variables, including computer self-efficacy, system quality, information quality, service quality, perceived usefulness, satisfaction, and continuance intention. The researcher applied a quantitative survey approach with 497 undergraduates with at least one semester of e-learning experience in the School of Civil Engineering, Architecture, and Environment, School of Food and Bioengineering, School of Law and Sociology, and School of Science of Chengdu Xihua University. The index of item-objective congruence (IOC) was applied and a pilot test (n=50) were conducted to evaluate the reliability using Cronbach's Alpha coefficient. Confirmatory factor analysis and structural equation modeling were employed in this study to assess the data, the validity, reliability, factor loadings, and the path coefficient. The results of the data analysis confirmed that perceived usefulness indicated the most powerful direct impact on satisfaction. In conclusion, administrators and teachers should pay adequate attention to computer self-efficacy, system quality, information quality, service quality, perceived usefulness and satisfaction that have had a substantial effect on students’ continuance intention to use e-learning platforms and consider the associated teaching reform in the future according to the findings of this research.